Measuring value-added-oriented BIM climate in construction projects: dimensions and indicators - Zhang, Lei; Yuan, Jingfeng; Xia, Nini; Ning, Yan; Ma, Junwei; Skibniewski, Mirosław J. (Journal of Civil Engineering and Management, 2020)
A value-added-oriented (VAO) BIM climate is the organizational climate of BIM value-added. However, a lack of research on VAO BIM climate has thwarted progress on BIM knowledge systems. By using the socio-technical systems approach and the competing value approach, 12 dimensions and 39 indicators of a VAO BIM climate are proposed and tested using 306 questionnaires collected from workers engaged in BIM construction projects across China. Data was analyzed by confirmatory factor analysis. The results show that the proposed dimensions and indicators are highly reliable and valid. The VAO BIM climate is heavily influenced by autonomy, career development, and task orientation. The top 10 indicators were mainly related to participation, task orientation, and goal effectiveness. And the MWD-BIM, RCS-BIM, CDMT-BIM, and SMD-BIM were mistaken as key indicators of participation, autonomy, peer relations, and organizational adaptability, respectively. The proposed dimensions and indicators can be used to advance scholarly understanding and theory on BIM climate in construction projects through directing resource allocation, enhancing the understanding of human–BIM interactions, improving the BIM knowledge system and facilitating decision framework of BIM adoption. Practical implications for managers in construction projects are provided in the end.